Regimes of youth transitions Choice, flexibility and security in young people’s experiences across different European contexts - Walther, Andreas (Young, 2006)
In a context of de-standardized transitions to work, young people are required to take more individual decisions, a process in which their subjectivities become increasingly important for social integration. While it can be assumed that this is a general trend, this article seeks to analyse the impact of different ‘transition regimes’ upon young people’s biographical experiences. Based on three comparative studies related to young people’s transitions to work, firstly, different ‘transition regimes’ are outlined, and secondly, the extent to which regime characteristics are reflected in young people’s accounts of their experiences is analysed; simultaneously, the underlying question of the extent to which young people perceive the possibilities of making subjectively meaningful choices is addressed, along with how this decision-making process is facilitated by flexibility and secured against the risk of failure and exclusion.
Keywords: jeunesse